Pengaruh Labelisasi Halal dan Kualitas Pelayanan terhadap Loyalitas Pelanggan pada Restoran Ta Wan di Kota Surabaya - Muna, Arina; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2024)
It is necessary for every culinary industry to guarantee halal products, especially restaurants that sell food from abroad. The purpose of this study was to determine the effect of halal labeling and service quality on customer loyalty at the Ta Wan restaurant in Surabaya City. This research method uses a quantitative method with an associative approach. Primary data sources through the distribution of online questionnaires. The sampling technique used in this study was a purposive non-probability technique, with 75 respondents and analyzed using SmartPLS 4.0. The results showed that halal labeling had a positive and significant effect on customer loyalty, service quality also had a positive and significant effect on customer loyalty. This study provides direct implications for restaurants if they want to maintain and attract Muslim customers, they need to pay attention to the halal label and service aspects. Ta Wan Restaurant can carry out marketing that emphasizes the importance of the halalness of their products and friendly and professional service, so that customers are more convinced in choosing the restaurant.